Evaluating the effectiveness of transport media on Shiga toxin-producing E. coli serotypes - Nicholas W. Baumann; A. West; Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 2014)
One of the key issues involved in accurately testing beef and the environment for the presence of specific bacteria, particularly pathogens such as Shiga toxin-producing Escherichia coli (STEC), is maintaining the viability of the microorganisms when transporting samples from the field to the laboratory. This process may take up to three days when considering collection, shipping and laboratory preparation times. Allowing the target bacteria to increase or decrease in numbers during transit is undesirable, so samples must be kept chilled and the media used for transport must offer a stable but non-nutritive environment. Three commonly used non-selective transport media were evaluated for their ability to maintain original STEC levels during transport. Holding temperature may vary during shipping, so this study evaluated two separate temperatures as co-variables.
Keywords: Cattlemen' s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen' s Day; Beef; Shiga toxin-producing E. coli; Transportation; Temperature